2004
DOI: 10.4141/a02-058
|View full text |Cite
|
Sign up to set email alerts
|

Expression of peroxisome proliferator-activated receptor (PPARγ) mRNA in adipose and muscle tissue of Holstein and Charolais cattle

Abstract: Expression of peroxisome proliferator-activated receptor (PPARγ) mRNA in adipose and muscle tissue of Holstein and Charolais cattle. Can. J. Anim. Sci. 84: 49-55. Peroxisome proliferator-activated receptor γ (PPARγ) regulates adipogenesis and lipid metabolism-related gene transcripts. The role, however, of PPARγ in different adipose depots and muscle in Holstein and Charolais cattle is still unclear. We used 20 animals (10 from each breed) for semiquantitative reverse transcription polymerase chain reaction (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Peroxisome proliferatoractivated receptor γ is a member of a subfamily of ligand-activated nuclear receptors that includes PPARα and PPARβ/δ (Fernyhough et al, 2007), and it plays a key role in adipocyte differentiation, fatty acid uptake, de novo fatty acid synthesis, and lipolysis and is the major regulator of lipid storage in the adipose tissue by modulating the expression of several genes involved in fatty acid metabolism (Feige et al, 2006). Results of the present study concur with those of Huff et al (2004), who did not fi nd differences in PPARγ gene expression between Charolais and Holstein cattle slaughtered at the same external fat thickness. Additionally, PPARγ2 is involved in adipose cells differentiation (Fernyhough et al, 2007), but Joseph et al (2010) suggested that the majority of adipocyte differentiation occurs within 8 mo of age in beef cattle; thus, it is plausible that the lack of an effect of bull breed on PPARγ2 expression was because bulls were greater than 8 mo of age at slaughter and the adipocyte differentiation was possibly complete.…”
Section: Resultssupporting
confidence: 88%
“…Peroxisome proliferatoractivated receptor γ is a member of a subfamily of ligand-activated nuclear receptors that includes PPARα and PPARβ/δ (Fernyhough et al, 2007), and it plays a key role in adipocyte differentiation, fatty acid uptake, de novo fatty acid synthesis, and lipolysis and is the major regulator of lipid storage in the adipose tissue by modulating the expression of several genes involved in fatty acid metabolism (Feige et al, 2006). Results of the present study concur with those of Huff et al (2004), who did not fi nd differences in PPARγ gene expression between Charolais and Holstein cattle slaughtered at the same external fat thickness. Additionally, PPARγ2 is involved in adipose cells differentiation (Fernyhough et al, 2007), but Joseph et al (2010) suggested that the majority of adipocyte differentiation occurs within 8 mo of age in beef cattle; thus, it is plausible that the lack of an effect of bull breed on PPARγ2 expression was because bulls were greater than 8 mo of age at slaughter and the adipocyte differentiation was possibly complete.…”
Section: Resultssupporting
confidence: 88%
“…PPARγ2 is able to promote adipocyte differentiation and lipid storage in white and brown adipose tissues (Vidal-Puig et al 1996). It is detected in buffalo (Huff et al 2004), and a positive relation is noted between mRNA abundance of PPARγ2 and IMF, which is consistent with our finding. Nevertheless, a negative association of PPARγ2 expression and IMF was noted in young sheep (Huang et al 2006) and goat (Li et al 2013) muscles, suggesting that PPARγ2 is likely involved in lipid dissipation in the skeletal muscles.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have also shown that PPARγ was an important candidate gene for IMF content in livestock and poultry (Gerbens et al 1998;Soret et al 1999;Gardan et al 2007). Polymorphisms in cattle PPARγ were found to be related to IMF content (Fan et al 2011); moreover, its expression level was positively correlated with muscle fat content in buffalo (Huff et al 2004). These studies indicate that PPARγ plays a key role in fat deposition and metabolism.…”
Section: Introductionmentioning
confidence: 75%
“…In previous studies it has been shown that this PPAR isotype is expressed in bovine aortic endothelial cells [46], beef cattle skeletal muscle (including intramuscular fat) [47], ovine intramuscular fat [48], bovine perimuscular preadipocytes [49], and bovine retinal pericytes [50]. In several beef cattle breeds, PPARG had a similar degree of expression in perirenal and omental adipose depots, followed by intramuscular fat and, in a minor quantity, in the longissimus muscle [47, 51]. …”
Section: Ppar Isotype Expression In Ruminant Tissuesmentioning
confidence: 99%